Cathepsins B1 and B2 of Trichobilharzia SPP., bird schistosomes causing cercarial dermatitis - Kašný, Martin; Mikeš, Libor; Dolečková, Kateřina; Hampl, Vladimír; Dvořák, Jan; Novotný, Marian; Horák, Petr (Advances in experimental medicine and biology, 2011)
Trichobilharzia regenti and T. szidati are schistosomes that infect birds. although T. regenti/T. szidati can only complete their life cycle in specific bird hosts (waterfowl), their larvae-cercariae are able to penetrate, transform and then migrate as schistosomula in nonspecific hosts (e.g., mouse, man). Peptidases are among the key molecules produced by these schistosomes that enable parasite invasion and survival within the host and include cysteine peptidases such as cathepsins B1 and B2. These enzymes are indispensable bio-catalysts in a number of basal biological processes and host-parasite interactions, e.g., tissue invasion/migration, nutrition and immune evasion. Similar biochemical and functional characteristics were observed for cathepsins B1 and B2 in bird schistosomes (T. regenti, T. szidati) and also for their homologs in human schistosomes (Schistosoma mansoni, S. japonicum). Therefore, data obtained in the research of bird schistosomes can also be exploited for the control of human schistosomes such as the search for targets of novel chemotherapeutic drugs and vaccines.
Keywords: ptáci; Animals; cerkárie; Humans; Amino Acid Sequence; Bird Diseases; lidé; Birds; Schistosoma; zvířata; molekulární sekvence - údaje; nemoci ptáků; Cathepsins; Cercaria; Molecular Sequence Data; kathepsiny; sekvence aminokyselin